Nonlinear robust precoding for coordinated multipoint transmission - Zhe-qi GU; Zhong-pei ZHANG (Tongxin xuebao)
A nonlinear robust precoding algorithm was proposed,which redesigned the feedback matrix，the forward matrix and the scaling matrix of the traditional tomlinson-harashima precoding algorithm based on the statistical characteristics of the downlink channel state information errors.Simulation results show that the nonlinear robust precoding algorithm can achieve better performance than the traditional linear and nonlinear precoding algorithms when the downlink channel state information errors exist.Due to the different downlink channel state information errors between user equipments in the coordinated multi-point transmission,the traditional “best-first” ordering algorithm was invalid.So an improved ordering algorithm was proposed to reduce the average bit error rate of the nonlinear robust precoding algorithm.